SYSTEMATIC AND DESCRIPTION OF NEW SPECIES OF MAXOMYS (MURIDAE) - Anang Setiawan Achmadi; Ibnu Maryanto; Maharadatunkamsi (Treubia, 2012)
We review the murid rodents of the genus Maxomys from Borneo, and recognise one new species, Maxomys tajuddinii sp. nov. The type locality is Empakuq village (1o 19â€™ 8.11â€ S, 120o 6â€™ 8â€ E), Melak District, Kutai, East Kalimantan, Indonesia. Descriptive and multivariate Analyses were used to reveal the variation and distinctive characters of this new species from its closest relatives. Results depicted that the morphology of new species M. tajuddinii sp. nov. resembles that of M. whiteheadi Thomas, 1894, which occurs throughout the Borneo island. Nine characters distinguish the new species: (1) sharp demarcation on the flanks between the dorsal and ventral pelage; (2) tail slightly similar to longer than head and body length, tapered and bicoloured, brownish black on dorsal surface and creamy white on ventral surface; (3) individual hairs covering head and body long, thick, and spinous, resulting in a dense pelage; (4) brownish orange buff dorsal pelage, with long, dense, spinous, black tipped guard hairs and creamy white ventral pelage; (5) rostrum long and narrow relative to overall skull size; (6) incisive foramina narrow relative to length, with posterior margins located slightly anterior to first molar; (7) first upper molar with three roots; (8) cusp t4 complete on first and second molars; and (9) 10 â€“ 12 scales per cm on tail. Morphologically, M. tajuddinii sp. nov. is unlike any other described species of Maxomys known to occur on Borneo. M. tajuddinii is the new species occurs in sympatry with M. whiteheadi Thomas, 1894 in peat swamp forests, logged mixed dipterocarp forests or waterlogged and periodically inundated sandy clay soil dominated by kerangas vegetation.